PENGARUH CORPORATE GOVERNANCE DAN AUDIT TENURE TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN LQ45 - Joshua Sanders Gunawan; Adji Suratman; Yuniza Rova (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
This study aims determine the effect of corporate governance and audit tenure on audit report lag on LQ45 companies listed on Indonesia Stock Exchange in 2016-2018. This research using secondary data. Sampling in this study using purposive sampling using predetermined criteria. Selected samples from companies that Included in LQ45 index on the Stock Exchange for 2016-2018 were 22 companies. The analysis technique used in this study is multiple Linear regression analysis and uses the Eviews version 9 application .The results of this study indicate that partially only internal audit variables have a significant effect on audit report lag, while the board of commissioners, audit committee and audit tenure have no significant effect on audit report lag.